1992
DOI: 10.1002/ange.19921040844
|View full text |Cite
|
Sign up to set email alerts
|

Carbenosmium‐Komplexe durch Zweifachmetallierung von Alkoxyalkyl‐ und Aminoalkylphosphanen

Abstract: Die Umwandlung einer Methoxy‐oder Methylamino‐Gruppe in einen Carben‐Liganden gelingt, wenn diese Teil eines Phosphans sind, So lassen sich in einer ergiebigen Eintopfsynthese die Komplex 1 und 2 aus OsCl3 · 3H2O bzw.[OsCl2(PPh3)3] und den phosphanen iPr2PCH2CH2Y (YOMe bzw. NMe2)herstellen. Mit dem Phosphan iPr2PCH2CO2Me kann ein Osmium(II)‐Komplex isoliert werden, der mit Phenylacetylen quantitativ zum Vinylidenkomplex 3 reagiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…While the osmium(IV) compounds 3, 4 as well as the osmium(II) complexes 7, 8 2 OMe}] by double metalation of the methoxy group of the phosphane. [5] The phosphane-amine iPr 2 PCH 2 -CH 2 NMe 2 behaves similarly.…”
Section: Introductionmentioning
confidence: 86%
“…While the osmium(IV) compounds 3, 4 as well as the osmium(II) complexes 7, 8 2 OMe}] by double metalation of the methoxy group of the phosphane. [5] The phosphane-amine iPr 2 PCH 2 -CH 2 NMe 2 behaves similarly.…”
Section: Introductionmentioning
confidence: 86%
“…We note that the chemistry of a manifold of osmium and ruthenium compounds with phosphane ethers, phosphane esters and phosphaneamines as ligands has recently been investigated in our laboratory as well as by others. [7,8] As a continuation of our earlier work, we report here the synthesis of a series of mono-, di-, tetra-and hexahydrido-…”
Section: Introductionmentioning
confidence: 99%
“…We note that the molecular structure of the related oxocarbene complex cis,cis-[OsCl 2 {κ 2 (C,P)-CHOCH 2 CH 2 PiPr 2 }{κ 2 (P,O)-iPr 2 -PCH 2 CH 2 OMe}] was determined crystallographically; the result confirmed that the two PiPr 2 units as well as the two chloro ligands are cis-disposed. [6] Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…As previously described, the oxocarbene-osmium ( [6] Since the yield of the product was significantly higher with OsCl 3 ·3H 2 O as the precursor, we first treated this compound with iPr 2 PCH 2 CH 2 NMe 2 . However, the reaction of OsCl 3 ·3H 2 O with iPr 2 PCH 2 CH 2 NMe 2 in 2-propanol under reflux gave a mixture of products which, based on the spectroscopic data, contained only about 40-50 % of the aminocarbene complex 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation